How entrepreneurial orientation stimulates creativity?: The mediating role of the meaning of work - Flores-Perez, Jorge Javier (2026)
Although Peruvian SMEs constitute an important support for the economy as job generators, they are vulnerable to survival due to the absence of knowledge about entrepreneurship and innovation strategies for their sustained growth. That is why this research had a double purpose, the first was to determine the impact of entrepreneurial orientation on the stimulation of creativity; and the second, analyze the mediating role of the meaning of work in the relationship between entrepreneurial orientation and the stimulation of creativity in employees of small and medium-sized companies in Peru. A quantitative epistemological paradigm with a post-positivist approach was adopted which provided the verification of the hypotheses derived from the theories with the hypothetical-deductive method. The simple random probabilistic sampling process was carried out in small and medium-sized enterprises (SMEs) in the manufacturing and commerce economic sectors in the Peruvian cities of Lima and Arequipa, takingemployees as units of analysis and from 148 companies, 348 were collected valid questionnaires. The results obtained showed, first, entrepreneurial orientation produces a direct, positive and significant effect on the stimulation of creativity. The evidence provided in this study verifies the mediating role of the effectiveness of work meaning in the relationship between entrepreneurial orientation and the stimulation of creativity.